The new regulation on travel authorization for minors and its negative effects on the best interests of the child - Shinno Pereyra, Vanessa Elizabeth (2025)
This paper aims to highlight the negative consequences arising from the impact on the best interests of the child due to the new regulation on notarized travel authorizations, which allows one parent to authorize travel under exceptional circumstances. These exceptional cases lack effective control parameters and include: (i) the presence of illnesses or treatments requiring medical care, supported by medical reports; (ii) when the child or adolescent must study abroad, whether for a student exchange program or a scholarship; and (iii) participation in academic or sports Olympiads. These exceptions lead to legal loopholes and pose risks of unjustified restrictions on parental authority (patria potestad), which is a right and duty shared by both parents. However, restoring or reclaiming this authority requires intervention by a specialized judge through lengthy and burdensome legal proceedings. Consequently, the main objective of this study is to assess the recent amendment to the travel authorization regulation. Secondary objectives include identifying the negative consequences of the amendment and proposing specific limits or documentation requirements to safeguard the best interests of the child. The paper concludes that this legislation produces adverse effects due to legal gaps that undermine the principle of the best interests of the child.